Design of an RTD-Integrated Slot Antenna for THz Oscillators - Shi, Xiuting (My University, 2026)
Terahertz (THz) oscillators are key components for future high-speed wireless communication systems, imaging, spectroscopy, and sensing applications. Resonant tunneling diodes (RTDs) are attractive THz sources due to their compact size, simple structure, and ability to generate oscillations at frequencies beyond the limits of conventional transistor technologies. To enable compact and easily integrated terahertz sources, RTDs are commonly combined with antenna structures that directly radiate the generated THz signals. This thesis presents the design and analysis of an RTD-integrated slot antenna oscillator operating near 650 GHz. An equivalent-circuit-based methodology is first employed to estimate the antenna dimensions from the RTD admittance characteristics. The slot antenna is then analysed using full-wave electromagnetic simulations, and its admittance is combined with a nonlinear RTD model. Oscillation conditions are evaluated through small-signal admittance analysis, while harmonic balance and transient simulations are used to verify large-signal oscillation behaviour. A complete oscillator model including parasitic elements and finite substrate effects is subsequently developed, followed by geometry optimisation of the slot antenna. The results show that the substrate primarily affects the real part of the oscillator admittance, while the imaginary part remains largely unchanged. Consequently, the oscillation frequency is preserved, whereas the output power is reduced due to decreased radiation efficiency. The optimised design achieves stable oscillation at approximately 646 GHz with an estimated radiated power of approximately 80 μW using a 0.49 μm2 RTD. The slot antenna exhibits a radiation efficiency of approximately 62%, and a peak directivity of approximately 6.8 dB without the use of a dielectric lens. The predicted radiated power is within the range reported for RTD oscillators operating in this frequency regime, although below the highest power reported for multi-element array implementations
Keywords: resonant tunneling diodes; terahertz oscillators